FoxP3+CD4+, IFN-γ+CD4+, and IFN-γ+CD8+ cell levels in erosive and non-erosive types of oral lichen planus patients - Andy Sun; Yu-Hsueh Wu; Julia Yu-Fong Chang; Yi-Ping Wang; Chun-Pin Chiang; Jean-San Chia (Elsevier, 2021)
Background/purpose: Oral lichen planus (OLP) is a localized autoimmune oral mucosal disease. This study evaluated whether different types of OLP patients including erosive OLP (EOLP), major EOLP, minor EOLP, and non-erosive OLP (NEOLP) patients had significantly higher percentages of FoxP3+CD4+ or IFN-γ+CD4+ cells in total CD4+ cells, and of IFN-γ+CD8+ cells in total CD8+ cells than healthy control subjects and whether the patient's age had significant influences on these cell percentages in OLP patients. Materials and methods: Flow cytometry was used to count the FoxP3+CD4+, IFN-γ+CD4+, or IFN-γ+CD8+ cell levels in 183 OLP patients (67 major EOLP, 81 minor EOLP, and 35 NEOLP patients) and 20 healthy control subjects. Results: Major EOLP patients had a significantly higher FoxP3+CD4+ cell percentage than health control subjects (P = 0.049) or minor EOLP patients (P = 0.008). Major EOLP patients had a significantly higher IFN-γ+CD4+ or IFN-γ+CD8+ cell percentage than healthy control subjects, NEOLP patients, or minor EOLP patients (all P-values < 0.01). In addition, both 61-80 year and 41-60 year OLP patients had significantly higher IFN-γ+CD8+ cell percentages than healthy control subjects or 20-40 year OLP patients (all P-values < 0.005). Conclusion: Major EOLP patients tend to have significantly higher percentages of FoxP3+CD4+, IFN-γ+CD4+, and IFN-γ+CD8+ cells than healthy control subjects, NEOLP patients or minor EOLP patients, suggesting that FoxP3+CD4+ Treg cells are increased to modulate OLP disease activity. Increased number of IFN-γ-producing activated T cell may be involved in oral epithelial cell destruction in OLP patients.